Comparison of segment masses between Japanese top senior and junior male gymnasts - Hakamada, N.; Funato, K.; Hirano, Y. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction Several studies have focused on anthropometry characteristics of gymnasts because they have specificity in body shape. Long-year training from childhood possibly may as to demonstrate the cause such a specific anthropometrical developments. In this study, we examined the difference in segment mass distribution between top Japanese senior and junior male gymnasts by means of three dimensional whole body scanning anthropometry. Methods Subjects were Japanese top male gymnasts (TG, age 23.0±3.0years, body height: 162.7±4.0cm, body mass: 55.0±2.4kg) and Japanese top junior male gymnasts (JTG, age 13.9±0.7years, body height: 143.3±9.0cm, body mass: 39.9±5.8kg). Whole body volumes were measured by using three dimensional whole body scanner (BLS: Hamamatsu Photonics KK). Scanning data obtained from BLS was divided in 17 parts of each segmental volume based on anatomical landmark point, and each segmental volume was calculated. Definition of each segment were same as C.E. Clauser,1969. Each segment mass (SM) by multiplying each segment volume and respective segment density was calculated. Relative SM to whole body mass (%SM) was also calculated. Results and discussion TG had a tendency to have significantly heavier SM for all segment except for hand, shank and foot. In relative SM to whole body mass (%SM), TG showed significantly larger values than JTG in neck + shoulder (TG: 10.16±0.87% vs. JTG: 7.70±1.04%), hip (TG: 19.20±3.38% vs. JTG: 24.04±1.66%) and upper arm segments (TG: 3.20±0.07% vs. JTG: 2.84±0.16%). It was suggested that large upper arm might one of the anthropometrics characteristics in gymnast which was clearly different in top and junior gymnasts. Larger trunk in top gymnasts was characterized by neck + shoulder and hip segment volume compared to junior gymnasts. Conclusion It was suggested that top gymnast were anthropometrically characterized as relatively large segmental mass in upper arm and trunk, particular in neck + shoulder and hip segments.